Massas digitais: Uma reflexão psicanalítica - Machado, Maria Rúbia Santos (Universidade Federal de São Carlos, 2021)
The book Group Psychology and the Analysis of the Ego (1921) completes 100 years and its theory is more present than ever. At a time when the dissemination of conversations and information is extremely facilitated by social networks, we can note that the formation of groups followed the same trend and, consequently, new symptoms are observed. The purpose of this study is to understand how the groups are constituted in social networks, to inquire about which figure guides these processes, and to assess possible effects of this influence. As a result, we propose parallels between groups and social networks and between group leaders and influencers. The reflections developed in this research open possibilities for new studies that aim to understand contemporary social and psychic formations.
Digital groups: A psychoanalytic reflection
Keywords: Psicanálise; Massas; Redes sociais; Líder; Influenciadores; Psychoanalysis; Groups; Social networks; Leader; Influencers; CIENCIAS HUMANAS::PSICOLOGIA::PSICOLOGIA SOCIAL::PROCESSOS GRUPAIS E DE COMUNICACAO